Cry, the Pea-cock, A perpetual meaning and value of life - Nayak, Dr. Felix (IJRDO-Journal of Applied Science, 2015)
Anita Desai’s characters are distinguished by the qualities of introspection, introversion and a refusal to surrender their individual selves. What one observes is a chain reaction of one leading to the other with the emerging picture of a battered and bruised individual writhing in pain and anguish. Thus Anita Desai’s novels indicate a shift from the external to the inner world of the individual. “ A marked leaning towards such an introversion is seen in Anita Desai’s writing”. 1 Her women protagonists, strive towards arriving at a more authentic way of life than the one which is available to them. 2 They in vain long for love and communion of the spirit which they perceive as the panaceas of the ills of the world. Their refusal to compromise and surrender and their inability to accept the perspective of their patrons inevitably result in isolation and loneliness. Lack of faith as well as lack understanding drive them to indulge in a futile search for fulfillment which is a mirage in the inhuman and materialistic world.